To find the equation of a linear function passing through the points (1, 4) and (-4, 6), first calculate the slope using the formula:
m = (y2 - y1) / (x2 - x1)
m = (6 - 4) / (-4 - 1)
m = 2 / -5
m = -2/5
Now that we have the slope, we can use the point-slope form of the equation of a line to get the equation:
y - y1 = m(x - x1)
y - 4 = -2/5(x - 1)
y - 4 = -2/5x + 2/5
y = -2/5x + 2/5 + 4
y = -2/5x + 2/5 + 20/5
y = -2/5x + 22/5
Therefore, the equation of the linear function passing through the points (1, 4) and (-4, 6) is:
y = -2/5x + 22/5
write the equation of the linear function that passes through the points (1, 4) and (-4, 6)
y = __x + __
1 answer